Faktor-Faktor yang Mempengaruhi Produktivitas Kerja Manajer dan Karyawan pada PT Indatex Palur di Karanganyar - Fammela, Fanny (2016)
This study aims to determine the effect of perceived Wages, Incentives perceived, Work Discipline and Motivation on Work Productivity both for managers and employees at PT IndatexPalur in Karanganyar. Hypotheses to the writer formulated in this research, namely There is significant influence between perceived Wages, Incentives perceived, Work Discipline and Motivation to Work Manager and Employee Productivity at PT IndatexPalur in Karanganyar. This research is empirical research using a survey method, in which the underlying data from a population sample was collected using a questionnaire instrument field. Samples in this study amounted to 15 managers and 236 employees. Sampling techniques in this study using purposive sampling method and incidental sampling. To answer this hypothesis using analysis tools classic assumption test, multiple linear regression with F test and t test, and the coefficient of determination (adjusted R2). These results indicate that the variables significantly influence the wages of labor productivity and variable wage managers perceived, perceived Incentives, Work Discipline and Motivation significant effect on employee productivity.